Phosphonomethoxyalkyl analogs of nucleotides - Holy, Antonín (Current pharmaceutical design, 2003)
Acyclic nucleoside phosphonates (ANP) are analogs of nucleotides exhibiting various biological (e.g. antiviral, cytostatic, antiparasitic, immunomodulatory) activities. This review describes synthetic approaches to their preparation, biological activities, structure-activity relationships and mode of action of ANPs, with emphasis to selected drugs or drug candidates. Three compounds of the ANP group (cidofovir, adefovir, tenofovir) are active components of potent antivirals approved for therapeutic use in human medicine aimed at hepatitis B, AIDS and various diseases caused by DNA viruses.
Keywords: DNA Virus Infections; vztahy mezi strukturou a aktivitou; Antiviral Agents; Drug Design; hepatitida B; Structure-Activity Relationship; Nucleotides; lidé; AIDS; organofosfonáty; Hepatitis B; Organophosphonates; racionální návrh léčiv; infekce DNA virem; antivirové látky; nukleotidy; Acquired Immunodeficiency Syndrome; Humans